Progress and outlook of submarine pipeline engineering technologies in China - Rong-qi CHEN; Zhen-ming LEI (You-qi chuyun, 2022)
Submarine pipelines are important means for offshore oil & gas transportation, and thus facilitating the development of submarine pipeline engineering technologies is of great significance to promote the development and construction of offshore oil and gas fields in China. Herein, the development status of submarine pipeline engineering technologies in China was expounded from the perspectives of the technical challenges faced by the submarine pipeline engineering, the development history and the progress of localization. In terms of technical challenges, the differences of the complex medium transported by submarine pipelines and the harsh marine, geological and geomorphic environments in China from those of international offshore oil and gas development were highlighted. In terms of development history, the development process of submarine pipeline industry in China was summarized and divided into five stages, i.e., the forming stage, the growth stage, the development stage, the expanding stage and the leap stage. Besides, the localization progress of submarine pipelines was traced back. In terms of engineering technology system, the development status of technologies was reviewed from the four points of gathering process, structure design, installation, and maintenance and emergency repair of China's submarine pipelines. Finally, the future development trend of submarine pipeline engineering technology and equipment in China was prospected.